PENGEMBANGAN MEDIA MONERGI (MONOPOLI ENERGI) UNTUK MENUMBUHKAN KEMAMPUAN PEMAHAMAN KONSEP IPA SISWA SD - Ulfaeni, Siti (Profesi Pendidikan Dasar, 2017)
This research applied media development monergi (monopoli energi) which helps the students understanding of science and how implementation media monergi (monopoli energi) be able to increase the students understanding in science.This subject of the research were students 3B grade, academic year 2016/2017 with total students 38.Â  The data from this research calculated by pretest and also posttest, questionnaire responds the students about the media. Questionnaire from expert validations media and also material. The scoring expert validations media and also material trough 2 steps, found from presentation from validation 1 and 2 that will be found the average presentation 77% with the criteria "valid" and 98% with the criteria "perfect", from the expert validations 1 and 2 we found the results that were 92% and 98% with the criteria is "perfect", and the result student responds about media monergi (monopoli energi) is 93% with "perfect" criteria. The result of student understanding concept pre-test was 49% and post-test was 84% there is enhancement. Therefore the capability of students understanding in science concept was increased. The conclusion was media learning of monergi (monopoli energi) valid to increase students understanding science concept the students 3B SDN sdn Pedurungan Kidul 02 Ssemarang.Keywords: research and development, monergi (monopoli energi), the ability in concept understanding